2019
DOI: 10.18048/2019.57.05.
|View full text |Cite
|
Sign up to set email alerts
|

On the Traveling Salesman Problem in Nautical Environments: an Evolutionary Computing Approach to Optimization of Tourist Route Paths in Medulin, Croatia

Abstract: The Traveling salesman problem (TSP) defines the problem of finding the optimal path between multiple points, connected by paths of a certain cost. This paper applies that problem formulation in the maritime environment, specifically a path planning problem for a tour boat visiting popular tourist locations in Medulin, Croatia. The problem is solved using two evolutionary computing methods – the genetic algorithm (GA) and the simulated annealing (SA) - and comparing the results (are compared) by an extensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Further research related to the observed system and its influence on the overall marine power plant performance will be performed by using various complex artificial intelligence methods and processes [59][60][61].…”
Section: Figure 7 -Energy and Exergy Efficiencies Of Superheated Stea...mentioning
confidence: 99%
“…Further research related to the observed system and its influence on the overall marine power plant performance will be performed by using various complex artificial intelligence methods and processes [59][60][61].…”
Section: Figure 7 -Energy and Exergy Efficiencies Of Superheated Stea...mentioning
confidence: 99%
“…After that, it will be investigated different system configurations with an aim to find an optimal one for each operating medium. All of newly obtained system configurations will be optimized by using various conventional [83,84] and artificial intelligence methods and techniques, which show its potential not only in marine applications [85,86], but also in energy systems [87], medical applications [88,89], robotics [90], in predicting trends of global (or local) diseases [91][92][93], etc.…”
Section: Figure 7 -Exergy Destructions (Exergy Losses) Of the Compone...mentioning
confidence: 99%
“…GA represents a meta-heuristic algorithm that is based on Darwin evolution theory [15]. This algorithm has a long history of utilization in various fields of science and engineering, ranging from robotics [16], through modelling of energy systems [17] to maritime affairs [18]. Such an approach can offer a simpler and more effective method for PID parametrization.…”
Section: Introductionmentioning
confidence: 99%